Respostas
respondido por:
2
-x² + x + 12
a= -1 b=1 c= 12
Δ=1² - 4 . -1 . 12
Δ=1 + 48
Δ=49
-1 +√49
-1 . 2
, -1 + 7 -1 - 7
-2 = -3 ---- -2 = +4
a= -1 b=1 c= 12
Δ=1² - 4 . -1 . 12
Δ=1 + 48
Δ=49
-1 +√49
-1 . 2
, -1 + 7 -1 - 7
-2 = -3 ---- -2 = +4
respondido por:
2
-x² + x + 12 = 0 (*-1)
x² - x - 12 = 0
Delta = b² - 4ac
Delta = 1 - 4(1)(-12)
Delta = 1 + 48
Delta = 49
X = (-b +- raiz delta) / 2a
X = (1 +- 7) / 2
x' = (1 + 7) / 2 = 8/2 = 4
x" = (1 - 7) / 2 = -6/2 = -3
x² - x - 12 = 0
Delta = b² - 4ac
Delta = 1 - 4(1)(-12)
Delta = 1 + 48
Delta = 49
X = (-b +- raiz delta) / 2a
X = (1 +- 7) / 2
x' = (1 + 7) / 2 = 8/2 = 4
x" = (1 - 7) / 2 = -6/2 = -3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás